2017
DOI: 10.1038/s41467-017-00337-6
|View full text |Cite
|
Sign up to set email alerts
|

Myosin efflux promotes cell elongation to coordinate chromosome segregation with cell cleavage

Abstract: Chromatid segregation must be coordinated with cytokinesis to preserve genomic stability. Here we report that cells clear trailing chromatids from the cleavage site by undergoing two phases of cell elongation. The first phase relies on the assembly of a wide contractile ring. The second phase requires the activity of a pool of myosin that flows from the ring and enriches the nascent daughter cell cortices. This myosin efflux is a novel feature of cytokinesis and its duration is coupled to nuclear envelope reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 79 publications
5
25
0
Order By: Relevance
“…1 C). This 36-s delay, although slight, is significant (P = 0.008 by a two-sided Mann–Whitney–Wilcoxon test) and in accordance with previous studies (Karg et al, 2015; Montembault et al, 2017). Given that initiation of sister acentric separation is delayed by ∼200 s (Fig.…”
Section: Resultssupporting
confidence: 92%
“…1 C). This 36-s delay, although slight, is significant (P = 0.008 by a two-sided Mann–Whitney–Wilcoxon test) and in accordance with previous studies (Karg et al, 2015; Montembault et al, 2017). Given that initiation of sister acentric separation is delayed by ∼200 s (Fig.…”
Section: Resultssupporting
confidence: 92%
“…We show that most actin rings are not inherited but form de novo in 16-cell-stage blastomeres via the action of cortical flows and a network of polar microtubules. Unlike well-described actin flows at the onset of cytokinesis directed toward the cytokinetic furrow (Reymann et al, 2016), the flow that forms the actin ring occurs following cytokinesis, likely due to disassembly of the actomyosin furrow (Montembault et al, 2017), and is directed away from the nascent junction toward the cell poles.…”
Section: Actin Ring Formation and Expansionmentioning
confidence: 80%
“…Alternatively, the abnormal localization of the anterior nucleus relative to the cytokinetic furrow could contribute to furrow repositioning. Indeed, previous work in Drosophila has shown that nuclei can regulate cortical cell shape changes by sequestering myosin regulators such as Ect2 (Montembault et al, 2017). However, preventing nuclear reformation by depleting the nucleoporin NPP-8 (Fig.S1C) does not prevent correction of DNA segregation defects or furrow displacement (Fig.S1D and legend, movie 10), indicating that the nuclei do not control furrow repositioning through the sequestration of myosin regulators.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, at the end of mitosis, the abscission checkpoint delays abscission, for instance when chromosomes are lagging within the intracellular bridge (Norden et al, 2006; Steigemann et al, 2009). Furthermore, it has been shown in Drosophila neuroblasts that trailing chromatids can regulate cortical myosin to induce cell shape changes and ensure proper chromatid segregation (Kotadia et al, 2012; Montembault et al, 2017). DNA segregation defects may also result from the lack of coordination between the positions of the mitotic spindle and the cytokinetic furrow.…”
Section: Introductionmentioning
confidence: 99%